Homomorphic phase boundary rare earth doped cesium zirconium fluoride-based up-conversion nano material
The synthesis of quasi-homotype rare earth doped zirconium fluoride cesium-based upconversion nanomaterials by high-temperature co-precipitation method has solved the problems of low luminescence efficiency and difficult to control the particle morphology of existing nanomaterials, and achieved significant improvement in the upconversion luminescence performance of nanomaterials, which is suitable for biomedical applications.
Patent Information
- Application Number
- CN202510047929.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-18
AI Technical Summary
Existing rare earth doped upconverted luminescent nanomaterials have low luminescence efficiency under laser irradiation, and their particle size and morphology are difficult to control, limiting their use in biological applications.
The high-temperature co-precipitation method was used to synthesize the quasi-homotype rare earth-doped zirconium fluoride cesium-based up-conversion nanomaterials. By controlling the concentration and reaction temperature of the precursor, nanomaterials with good crystallinity and uniform particle size distribution were obtained.
It significantly enhances the upconversion luminescence performance of nanomaterials, has uniform particle size distribution and good dispersion, and is suitable for biomedical imaging and biomarking fields.
Smart Images

Figure CN119842399A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a morphotropic phase boundary rare earth doped zirconium fluoride-based up-conversion nano material, belonging to the technical field of nano luminescent materials. Background Art
[0002] Rare earth doped upconversion luminescent nanomaterials have the advantages of low toxicity, resistance to photobleaching, weak background interference, long fluorescence lifetime, low excitation energy and deep tissue penetration, thus showing broad application prospects in the fields of lighting display, drug delivery, biomedical imaging, biomarkers, etc., and have become a research hotspot at home and abroad in recent years. Rare earth doped nanoluminescent materials are composed of matrix materials and rare earth doped ions. The upconversion luminescent matrix is mainly concentrated in the phonon with lower energy (<500cm -1 ) and fluorides with better stability. In the past few decades, hexagonal β-NaYF4 has been considered the best matrix material. In 2015, Professor Xiong Yujie of the University of Science and Technology of China found that at 600W cm -2 Under 980nm laser irradiation, the hexagonal phase NaYF4 undergoes a phase change and transforms into a new cubic phase NaYF4 (whose atomic arrangement is different from the cubic phase α-NaYF4), and its luminescence efficiency reaches 8.2%. However, this new cubic phase NaYF4 particle can only be obtained by laser heating, and the particle size and morphology are difficult to control. In addition, it is micron-sized and has an irregular morphology, which is not suitable for biological applications. In the past, people have been committed to the research of pure phase matrix materials, but the low upconversion efficiency is the bottleneck for its application, and we believe that non-pure phase matrix materials can better enhance the upconversion luminescence. The present invention proposes a new type of quasi-isotropic phase boundary matrix material, which realizes the upconversion luminescence of non-pure phase-significantly enhanced upconversion nanomaterials. Summary of the invention
[0003] The present invention relates to a method for preparing a quasi-morphous phase boundary rare earth doped zirconium fluoride-based upconversion nanomaterial. Compared with its pure phase, the material can significantly enhance its upconversion luminescence, and can synthesize a quasi-morphous phase boundary nanomaterial with good crystallization performance through high-temperature coprecipitation. The nanomaterial has uniform particle size distribution, good dispersibility, and good upconversion luminescence performance. By controlling the concentration of the precursor and the reaction temperature, reaction time and other parameters, quasi-morphous phase boundary upconversion nanomaterials of different sizes and morphologies can be obtained.
[0004] The technical solution of the present invention is as follows:
[0005] A zirconium fluoride-cesium benchmark isotype phase boundary upconversion nanomaterial, characterized in that one nanocrystal includes two different phases at the same time.
[0006] According to the present invention, the morphotropic phase boundary upconversion nanocrystals cause the pure phase unit cell to produce a phase different from the original phase, thereby resulting in a significant enhancement of the upconversion luminescence of the nanocrystals.
[0007] According to the present invention, the synthesis of 1mmol of luminescent material in the quasi-morphous phase boundary nanocrystals, ytterbium ions (Yb 3+ ) and erbium ions (Er 3+ ) are doped in an amount of 5-30%, 0.5-5%, preferably 10-20% and 0.5-2%.
[0008] The present invention also provides a method for preparing the above-mentioned rare earth-doped zirconium fluoride-based upconversion nanomaterial at the morphotropic phase boundary, comprising the following parts:
[0009] (1) Preparation of the hexagonal phase Cs2ZrF6:Yb 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ Nanocrystals with morphotropic phase boundaries;
[0010] (2) Preparation of the hexagonal phase Cs2ZrF6:Yb 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ +Li4ZrF8:Yb 3+ / Er 3+ Nanocrystals with morphotropic phase boundaries.
[0011] According to the present invention, the partially morphotropic phase boundary nanocrystals are prepared by a high temperature co-precipitation method.
[0012] The method comprises: mixing a certain ratio of zirconium acetylacetonate, ytterbium acetate, erbium acetate, cesium carbonate, lithium carbonate and a mixed solvent of oleic acid and octadecene, heating the mixture to 120-160°C to completely dissolve the solids, cooling the mixture to room temperature, adding a methanol solution containing ammonium fluoride, heating the mixture to 50-70°C in an inert gas atmosphere to discharge methanol, heating the mixture to 250-310°C to react, cooling, washing and drying the mixture, and finally obtaining quasi-isotropic phase boundary nanocrystals.
[0013] According to the present invention, the hexagonal phase Cs2ZrF6:Yb 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+The specific preparation of the quasi-isotropic phase boundary nanocrystals includes: weighing a certain ratio of zirconium acetylacetonate, ytterbium acetate, erbium acetate, cesium carbonate, and lithium carbonate into a reaction container at room temperature, adding a mixed solvent of oleic acid and octadecene, heating to 120-160° C. under an inert atmosphere, completely dissolving the above solids and then cooling to room temperature, then adding an appropriate amount of methanol solution containing ammonium fluoride, heating to 50-70° C. under an inert atmosphere, keeping the temperature until the methanol is completely removed, continuing to heat to 100-110° C., keeping the temperature until the water is completely removed, and finally heating to 250-310° C., naturally cooling to room temperature 60 minutes after the reaction is completed, precipitating and washing to obtain a hexagonal phase Cs2ZrF6:Yb 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ of morphotropic phase boundary nanocrystals.
[0014] According to the present invention, the amount of each ion required in the zirconium acetylacetonate, ytterbium acetate, erbium acetate, ammonium fluoride, cesium carbonate and lithium carbonate weighed in the above steps is 0.65-0.945 mmol Zr 4+ :1.14~1.8mmol Li + ; 0.05~0.3mmolYb 3+ :0.005~0.05mmol Er 3+ :6mmol F - :1.2-1.86mmol Cs + Among them, Zr 4+ +Yb 3+ +Er 3+ =1mmol; Li + +Cs + =3mmol. Preferably 0.2mmol Yb 3+ ; 0.02mmol Er 3+ ; 0.78mmol Zr 4+ ; 1.35mmol Li + +; 1.65mmol Cs + ; 6mmol F - .
[0015] According to the present invention, the amounts of oleic acid and octadecene in the mixed solvent in the above step are 8 mL oleic acid: 12 mL octadecene.
[0016] According to the present invention, the amount of methanol used to dissolve the fluorine source in the above step is 15 ml.
[0017] According to the present invention, the reaction temperature in the above steps is preferably 280°C.
[0018] According to the present invention, the hexagonal phase Cs2ZrF6:Yb 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ +Li4ZrF8:Yb 3+ / Er 3+ The specific preparation of the quasi-isotropic phase boundary nanocrystals includes: weighing a certain ratio of zirconium acetylacetonate, cesium carbonate, lithium carbonate, ytterbium acetate, and erbium acetate into a reaction container at room temperature, adding a mixed solvent of oleic acid and octadecene, heating to 120-160° C. in an inert atmosphere to completely dissolve the above solids, and then cooling to room temperature, then adding an appropriate amount of methanol solution containing ammonium fluoride, heating to 50-70° C. in an inert atmosphere, keeping the temperature until the methanol is completely removed, continuing to heat to 100-110° C., keeping the temperature until the water is completely removed, and finally heating to 250-310° C., naturally cooling to room temperature 60 minutes after the reaction is completed, precipitating and washing, to obtain a hexagonal phase Cs2ZrF6:Yb 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ +Li4ZrF8:Yb 3+ / Er 3+ Morphotropic phase boundary nanocrystals.
[0019] According to the present invention, the amount of each ion required in the above steps of zirconium acetylacetonate, ytterbium acetate, erbium acetate, ammonium fluoride, cesium carbonate and lithium carbonate is 0.65-0.945 mmol Zr 4+ :1.14~1.8mmol Li + ; 0.05~0.3mmol Yb 3 + ; 0.005~0.05mmol Er 3+ ; 6mmol F - :1.2-1.86mmol Cs + Among them, Zr 4+ +Yb 3+ +Er 3+ =1mmol; Li + +Cs + =3mmol. Preferably 0.2mmol Yb 3+ ; 0.02mmol Er 3+ ; 0.78mmol Zr 4+ ; 2.1mmol Li + +; 0.9mmol Cs + ; 6mmol F - .
[0020] According to the present invention, the amounts of oleic acid and octadecene in the mixed solvent in the above step are 8 mL oleic acid: 12 mL octadecene.
[0021] According to the present invention, the amount of methanol used to dissolve the fluorine source in the above step is 15 ml.
[0022] According to the present invention, the reaction temperature in the above steps is preferably 280°C.
[0023] Compared with the existing method for enhancing up-conversion luminescence, the beneficial effects of the present invention are:
[0024] The present invention adopts a high-temperature co-precipitation method to synthesize a rare earth-doped Cs2ZrF6 upconversion luminescent matrix material with a quasi-isotropic phase boundary. The synthesis conditions are easy to control and have good repeatability. The prepared luminescent nanomaterial has good dispersibility and uniformity, and has good upconversion luminescent performance. It can generate light of different wavelengths under 980nm laser excitation, and has great development potential in the fields of luminescent imaging and biological applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is the pure phase Cs2ZrF6:Yb in Example 1 of the present invention. 3+ / Er 3+ X-ray powder diffraction pattern of upconversion nanocrystals.
[0026] Figure 2 It is the pure phase Cs2ZrF6:Yb in Example 1 of the present invention. 3+ / Er 3+ Transmission electron microscopy image of upconversion nanocrystals.
[0027] Figure 3 It is the pure phase Cs2ZrF6:Yb in Example 1 of the present invention. 3+ / Er 3+ Upconversion emission spectrum of upconversion nanocrystals under 980nm laser excitation.
[0028] Figure 4 It is the morphotropic phase boundary Cs2ZrF6:Yb in Example 2 of the present invention. 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ X-ray powder diffraction pattern of upconversion nanocrystals.
[0029] Figure 5 It is the morphotropic phase boundary Cs2ZrF6:Yb in Example 2 of the present invention. 3+ / Er 3+ +Li3Zr4F 19 :Yb3+ / Er 3+ Transmission electron microscopy images of upconversion nanocrystals at different resolutions.
[0030] Figure 6 It is the morphotropic phase boundary Cs2ZrF6:Yb in Example 2 of the present invention. 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ Upconversion emission spectra of upconversion nanocrystals excited by a low-power-density 980nm laser.
[0031] Figure 7 It is the morphotropic phase boundary Cs2ZrF6:Yb in Example 3 of the present invention. 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ +Li4ZrF8:Yb 3+ / Er 3+ X-ray powder diffraction pattern of upconversion nanocrystals.
[0032] Figure 8 It is the morphotropic phase boundary Cs2ZrF6:Yb in Example 3 of the present invention. 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ +Li4ZrF8:Yb 3+ / Er 3+ Transmission electron microscopy images of upconversion nanocrystals at different resolutions.
[0033] Fig. 9 It is the morphotropic phase boundary Cs2ZrF6:Yb in Example 3 of the present invention. 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ +Li4ZrF8:Yb 3+ / Er 3+ Upconversion emission spectrum of upconversion nanocrystals under 980nm laser excitation.
[0034] Fig.10 The concentration of Li + The variation trend of the emission spectrum intensity of the doping and the comparison and enhancement multiples of the emission light intensity of Examples 1, 2, and 3. DETAILED DESCRIPTION
[0035] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. However, these embodiments should not be interpreted as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope of protection intended by the present invention.
[0036] Example 1
[0037] Preparation of pure phase Cs2ZrF6 upconversion nanocrystals by high temperature coprecipitation method:
[0038] At room temperature, 0.3921 g of zirconium acetylacetonate, 0.0844 g of ytterbium acetate, 0.0069 g of erbium acetate, and 0.4937 g of cesium carbonate were weighed into a three-necked flask, 8 mL of oleic acid and 12 mL of octadecene were added as solvents, and the mixture was heated to 140° C. under an inert atmosphere to completely dissolve the solids, and then naturally cooled to room temperature to obtain a clear solution; 15 mL of a methanol solution containing 0.2222 g of ammonium fluoride was added to the solution, and the mixture was heated to 50-70° C. under an inert atmosphere, and kept warm until the methanol was completely removed, and then heated to 100-110° C., and kept warm until the water was completely removed, and then heated to 280° C. under an inert atmosphere, and kept warm for 60 minutes, and then naturally cooled to room temperature, precipitated, and washed to obtain pure phase Cs2ZrF6:Yb 3+ / Er 3+ Nanocrystals.
[0039] from Figure 1 It can be seen that the nanocrystal has good crystallinity, and the position and relative intensity of the diffraction peak of the main phase are consistent with the PDF standard card of Cs2ZrF6 (JCPDS No.74-0173), belonging to the hexagonal crystal system.
[0040] like Figure 2 As shown, the nanocrystals have good dispersion, uniform morphology, and a particle size of about 17.5 nm.
[0041] like Figure 3 As shown, under the excitation of 980nm light source, the oil-soluble nanocrystals emit a main peak at 656nm, corresponding to Er 3+ ion 4 F 9 / 2 - 4 I 15 / 2 Electric dipole transition.
[0042] Example 2
[0043] Preparation of Cs2ZrF6:Yb at the quasi-isotropic phase boundary by high temperature coprecipitation 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ Upconversion nanocrystals:
[0044] At room temperature, 0.3921 g of zirconium acetylacetonate, 0.0844 g of ytterbium acetate, 0.0069 g of erbium acetate, 0.0499 g of lithium carbonate, and 0.2688 g of cesium carbonate were weighed into a three-necked flask, 8 mL of oleic acid and 12 mL of octadecene were added as solvents, and the mixture was heated to 140° C. under an inert atmosphere to completely dissolve the solids, and then naturally cooled to room temperature to obtain a clear solution; 15 mL of a methanol solution containing 0.2222 g of ammonium fluoride was added to the solution, and the mixture was heated to 50-70° C. under an inert atmosphere, and kept warm until the methanol was completely removed, and then heated to 100-110° C., and kept warm until the water was completely removed, and then heated to 280° C. under an inert atmosphere, and kept warm for 60 minutes, and then naturally cooled to room temperature, precipitated and washed to obtain Cs2ZrF6:Yb 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ Nanocrystals.
[0045] from Figure 4 It can be seen that the nanocrystal has good crystallinity, and the position and relative intensity of the diffraction peak of the main phase are consistent with the PDF standard card of Cs2ZrF6 (JCPDS No.74-0173), belonging to the hexagonal crystal system.
[0046] like Figure 5 As shown, the nanocrystals have good dispersion, uniform morphology, and a particle size of about 27.5 nm.
[0047] like Figure 6 As shown, under the excitation of 980nm light source, the oil-soluble nanocrystals emit red upconversion luminescence with a main peak at 656nm, corresponding to Er 3+ ion 4 F 9 / 2 - 4 I 15 / 2 Electric dipole transition.
[0048] Example 3
[0049] Preparation of Cs2ZrF6:Yb with quasi-isotropic phase boundary by high temperature coprecipitation method 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ +Li4ZrF8:Yb 3+ / Er 3+ Upconversion nanocrystals:
[0050] At room temperature, 0.3921 g of zirconium acetylacetonate, 0.0844 g of ytterbium acetate, 0.0069 g of erbium acetate, 0.0766 g of lithium carbonate, and 0.1466 g of cesium carbonate were weighed into a three-necked flask, 8 mL of oleic acid and 12 mL of octadecene were added as solvents, and the mixture was heated to 140° C. under an inert atmosphere to completely dissolve the solids, and then naturally cooled to room temperature to obtain a clear solution; 15 mL of a methanol solution containing 0.2222 g of ammonium fluoride was added to the solution, and the mixture was heated to 50-70° C. under an inert atmosphere, and kept warm until the methanol was completely removed, and then heated to 100-110° C., and kept warm until the water was completely removed, and then heated to 280° C. under an inert atmosphere, and kept warm for 60 minutes, and then naturally cooled to room temperature, precipitated and washed to obtain Cs2ZrF6:Yb 3+ / Er 3+ +Li3Zr4F 19 :Yb 3+ / Er 3+ +Li4ZrF8:Yb 3+ / Er 3+ Nanocrystals.
[0051] from Figure 7 It can be seen from the figure that the nanocrystal has good crystallinity, and the position and relative intensity of the diffraction peak of the main phase are consistent with the PDF standard card of Cs2ZrF6 (JCPDS No . 74-0173) and belongs to the hexagonal crystal system.
[0052] like Figure 8 As shown, the nanocrystals have good dispersibility, uniform morphology, and a particle size of about 90 nm.
[0053] like Fig. 9 As shown, under the excitation of 980nm light source, the oil-soluble nanocrystals emit red upconversion luminescence with a main peak at 656nm, corresponding to Er 3+ ion 4 F 9 / 2 - 4 I 15 / 2 Electric dipole transition.
[0054] from Fig.10 It can be seen that Li + The luminescence intensity increases suddenly when the doping concentration is 45% and 70%, and its luminescence intensity is 155 and 185 times that of the pure phase respectively.
Claims
1. A quasi-morphous phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial, characterized in that The quasi-morphous phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial is + There is a quasi-modal phase boundary under doping.
2. The morphotropic phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial according to claim 1, characterized in that Morphotropic phase boundary Cs2ZrF6+Li3Zr4F 19 / Cs2ZrF6+Li3Zr4F 19 +Li4ZrF8 nanocrystals are formed by changing Li + This is achieved by the doping ratio.
3. The morphotropic phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial according to claim 2, characterized in that Li doping + The ratio ranges from 0% to 100%.
4. The morphotropic phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial according to claim 2, characterized in that The morphotropic phase boundary comprises the following two materials: (1) Hexagonal phase Cs2ZrF6+Li3Zr4F 19 :Yb / Er nanocrystals; (2) Hexagonal phase Cs2ZrF6+Li3Zr4F 19 +Li4ZrF8:Yb / Er nanocrystals.
5. The method for preparing the morphotropic phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial according to claim 1, characterized in that The process steps are: a) First, prepare a fluorine source, using ammonium fluoride as the solute and volatile methanol as the solvent. b) Then weigh a certain proportion of cesium carbonate, zirconium acetylacetonate, lithium carbonate, ytterbium acetate and erbium acetate and add them to a mixed solvent of oleic acid and octadecene, and completely dissolve the raw materials in a three-necked flask. After cooling, add a) and react at a certain temperature after the volatile solvent in a) is completely evaporated. After the reaction is completed, cool to room temperature. c) The product after the reaction was precipitated with ethanol in an amount equal to that of the solvent, and washed by centrifugation three times. d) The final product after centrifugation is placed in an oven and dried for 24 hours to obtain the desired product.
6. The method for preparing the morphotropic phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial according to claim 5, characterized in that The quasi-modular phase boundary can be obtained by controlling different doping ratios, reaction temperatures and reaction times. According to the present invention, the amount of each element in zirconium acetylacetonate, ytterbium acetate, erbium acetate, ammonium fluoride, cesium carbonate and lithium carbonate is 0.65-0.945 mmol zirconium; 0.05-0.3 mmol ytterbium; 0.005-0.05 mmol erbium; 6 mmol fluorine; 0-3 mmol cesium; 0-3 mmol lithium. According to the present invention, the entire process of dissolving, removing methanol, reacting, cooling, etc. is carried out under an inert atmosphere. According to the present invention, the mixing and dissolving is carried out by heating to 120-160° C. under an inert atmosphere and stirring for 0.5-1 hour. According to the present invention, the methanol removal process is kept at 50-70°C for 30-40 minutes, and more preferably, kept at 100-110°C for another 10 minutes. According to the present invention, the reaction temperature is 250-310° C. and the reaction time is 60 minutes. According to the present invention, after cooling, ethanol in an amount equal to that of the solvent is used as a precipitant for precipitation for five minutes, followed by centrifugation, washing twice with cyclohexane and ethanol, and drying for 24 hours.
7. The method for preparing the morphotropic phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial according to claim 5, characterized in that The preparation method is a high temperature co-precipitation method.
8. The method for preparing the morphotropic phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial according to claim 5, characterized in that The amounts of oleic acid and octadecene in the mixed solvent are 8 mL of oleic acid and 12 mL of octadecene, and the amount of methanol solvent for dissolving the fluorine source is 15 mL.
9. The morphotropic phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial according to claim 1, characterized in that The rare earth-doped cesium zirconium fluoride-based material is a nano-luminescent material, which can be used as an ideal matrix material for up-conversion and down-conversion luminescence; preferably, it is used in the fields of luminescent imaging, anti-counterfeiting, and biological applications.
10. The morphotropic phase boundary rare earth doped zirconium fluoride cesium based upconversion nanomaterial according to claim 1, characterized in that The quasi-modular phase boundary obtained by doping can increase the luminescence intensity by 155 and 185 times compared with the pure substance.